Proceedings of the 2014 International Conference on Mechatronics, Electronic, Industrial and Control Engineering 2014
DOI: 10.2991/meic-14.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcination Temperature on the Structure and CO2 Sorption Properties of Li4SiO4 Sorbents from Rice Husk Ash

Abstract: Abstract-Highly efficient Li 4 SiO 4 -based sorbents for CO 2 capture at high temperature, were developed using waste rice husk ash (RHA). Two different RHAS resulted from different calcination temperature as raw materials for preparing the Li 4 SiO 4 -based sorbents. These raw ashes and their resulting Li 4 SiO 4 -based sorbents were characterized by X-ray diffraction, thermogravimetry (dynamic and isothermically), and nitrogen adsorption. CO 2 sorption stability was investigated in a dual fixed-bed reactor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They reported a weight gain of nearly 135 % over 15 cycles, which was much higher than that of pure Li 4 SiO 4 material. Furthermore, Wang et al [ 58 ] pretreated rice husk samples at 600 and 1000 °C, respectively, and cyclic performances of the two RHA-synthesized Li 4 SiO 4 materials pretreated at 1000 °C achieved better CO 2 absorption performance, which was similar to that of the RHA-derived Li 4 SiO 4 material mentioned above. To study the effects of RHA as the silicon precursor on the CO 2 absorption properties of Li 4 SiO 4 material, Wang et al [ 59 ] selected RHA and two kinds of nanosilica (Aerosil and quartz) to prepare Li 4 SiO 4 materials by solid-state reaction method, and SEM images and BET analysis indicated that RHA-synthesized Li 4 SiO 4 material possessed higher surface area and larger pore volume.…”
Section: Synthesis Of LI 4 Sio 4 mentioning
confidence: 74%
“…They reported a weight gain of nearly 135 % over 15 cycles, which was much higher than that of pure Li 4 SiO 4 material. Furthermore, Wang et al [ 58 ] pretreated rice husk samples at 600 and 1000 °C, respectively, and cyclic performances of the two RHA-synthesized Li 4 SiO 4 materials pretreated at 1000 °C achieved better CO 2 absorption performance, which was similar to that of the RHA-derived Li 4 SiO 4 material mentioned above. To study the effects of RHA as the silicon precursor on the CO 2 absorption properties of Li 4 SiO 4 material, Wang et al [ 59 ] selected RHA and two kinds of nanosilica (Aerosil and quartz) to prepare Li 4 SiO 4 materials by solid-state reaction method, and SEM images and BET analysis indicated that RHA-synthesized Li 4 SiO 4 material possessed higher surface area and larger pore volume.…”
Section: Synthesis Of LI 4 Sio 4 mentioning
confidence: 74%
“…Carbon fibers are filaments, lines, or reels that contain more than 92 percent carbon and are normally in a nongraphite condition, according to the International Union of Pure and Applied Chemistry (IUPAC) [1] . This means that carbon is defined as a two-dimensional long-range arrangement of carbon atoms in planar hexagonal networks with no crystalline structure in the third direction except for some parallel stacking [2] . Graphite fiber, often known as carbon fiber (CF), is a strong, lightweight material that can be used for both structural and non-structural applications (e.g., thermal insulation).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibers are filaments, lines, or reels that contain more than 92 percent carbon and are normally in a non-graphitic condition, according to the International Union of Pure and Applied Chemistry (IUPAC) [5]. This means that carbon is defined as a two-dimensional long-range arrangement of carbon atoms in planar hexagonal networks with no crystalline structure in the third direction except for some parallel stacking [6]. Carbon fiber (CF), also known as graphite fiber, is a lightweight, durable, and flexible material that can be utilized for both structural and non-structural purposes (e.g., thermal insulation).…”
Section: Introductionmentioning
confidence: 99%